1990
DOI: 10.1007/bf00686237
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of high-dose cisplatin and cyclophosphamide with glutathione protection in the treatment of bulky advanced epithelial ovarian cancer

Abstract: Recent efforts to improve the response rates in advanced ovarian cancer with the use of high-dose cisplatin have been limited by unacceptable toxicity. Based on experimental and clinical studies indicating that reduced glutathione (GSH) is a protective agent against cisplatin-induced toxicity, a new high-dose regimen including GSH as a chemoprotector was designed in an attempt to improve the efficacy and therapeutic index of cisplatin. A total of 40 consecutive patients with stage III (bulky) and IV ovarian ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…Generally, cisplatin is concentrated at higher levels in the dorsal root ganglion cells and causes apoptosis of sensory neurons [42,43]. Various attempts have been reported to reduce the neuropathy associated with cisplatin, and some agents have been reported to be promising for neuroprotection [44,45]. Among these medications, the incidence of clinical neuropathy was reported at 44% after a cumulative cisplatin dose of 400 mg/m 2 and at 88% after 600 mg/m 2 [16].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, cisplatin is concentrated at higher levels in the dorsal root ganglion cells and causes apoptosis of sensory neurons [42,43]. Various attempts have been reported to reduce the neuropathy associated with cisplatin, and some agents have been reported to be promising for neuroprotection [44,45]. Among these medications, the incidence of clinical neuropathy was reported at 44% after a cumulative cisplatin dose of 400 mg/m 2 and at 88% after 600 mg/m 2 [16].…”
Section: Discussionmentioning
confidence: 99%
“…Other toxic effects of cisplatin also markedly increased with higher doses of cisplatin (Bodenner et al 1986;Hamers et al 1993;Rybak et al 1995). Nephroprotection by various chemotherapeutic agents is being evaluated against higher doses of cisplatin in clinical practice (Cozzaglio et al 1990;Di Re et al 1990;Fontanelli et al 1992). Therefore, this study evaluates the nephroprotective effects of a biological antioxidant lipoic acid against the toxic renal effects that occur with higher doses of cisplatin in rats.…”
Section: Discussionmentioning
confidence: 99%
“…GSH is reported to diminish cisplatin-induced neurotoxicity, and patients treated with cisplatin in combination with GSH (doses ranging from 1.5 to 3 g/m 2 ) exhibit a less severe neuropathic syndrome with no negative interference of its anticancer activity in these patients (Cavaletti et al, 1996;Colombo et al, 1995;Di Re et al, 1993). Experimental studies performed on rats have shown that GSH provides protection against the cisplatininduced slowing of sensory nerve conduction velocity without interfering with the antitumour ecacy of this drug (Hamers et al, 1993).…”
Section: Discussionmentioning
confidence: 99%